Real-world experience of diagnosis, disability, and daily management in parents of children with different genetic developmental and epileptic encephalopathies: a qualitative study - Cristina Garcia-Bravo; Domingo Palacios-Ceña; Ángel Aledo-Serrano; Javier Güeita-Rodríguez; Juan Francisco Velarde-García; Juan Nicolas Cuenca-Zaldivar; Romain Marconnot; María Cristina Alonso-Blanco; Jorge Pérez-Corrales; Carmen Jimenez-Antona (Annals of Medicine)
Purpose This study describes the experience of parents of children with developmental and epileptic encephalopathies (DEE) and how the disease impacts their daily lives.Materials and methods A descriptive qualitative study was conducted using purposeful sampling. Twenty-one parents of children with DEEs caused by SCN1A, KCNQ2, CDKL5, PCDH19, and GNAO1 variants were included. Data collection was based on in-depth interviews and researchers’ field notes. An inductive thematic analysis was performed.Results Five themes emerged: (a) the diagnostic process, which describes the path from the time parents recognize the first symptoms until diagnostic confirmation is obtained; (b) the relationship with health professionals during the search for a diagnosis, which describes how the entire process is conditioned by the relationships established; (c) the world of disability, revealing how the disease and disability impact the life of the parents; (d) living day to day, the parents continuously change their plans in anticipation of the onset of a seizure; (e) the disease progression, a cause of great concern in the parents.Conclusions Our results show the need to develop recovery programs that integrate health and social interventions to support parents of children with DEE in the process of diagnosis and disease management.